Cloud computing: Its development and security - Mudge, J. Craig (Journal of Telecommunications and the Digital Economy, 2019)
Cloud computing is a mode of acquisition of infrastructure where a cloud service provides on demand computing and on-demand storage, accessible over the web, with a matching business model, namely pay-per-use. Lower cost, sometimes a factor of five, is achieved by automating operations in warehouse-sized data centres, sharing the hefty burden of cooling, physical security, and power backup, and the use of commodity components. As access to storage managed by cloud service providers gained market acceptance, the phrase “the cloud” came into use to refer to the location of information stored with a cloud service provider to be shared (business documents and photos) or copied for backup (against losing a phone or deleting information on a laptop). Security, and to a lesser extent privacy, concerns are the major barriers to the adoption of cloud computing, but the leading cloud service providers have responded to the point that sensitive information, such as medical records and credit-card-holder data, is now held in the cloud.